Patient satisfaction towards composite and amalgam restorations in IIUM dental polyclinic - Anisa Kusumawardani; Susi Sukmasari; Norhazayti Ab Halim; Raja Hazwani Binti Raja Nhari; Siti Aisah Binti Abdul Habi (Wolters Kluwer Medknow Publications, 2020)
Background: Dentistry continues to evolve with the development of restorative materials. Patient satisfaction is an increasingly significant issue in dental practice; therefore, knowledge of the level of patient satisfaction with restorative materials is important. Objectives: The objective was to assess patient satisfaction with composite and amalgam restorations carried out by International Islamic University Malaysia (IIUM) dental students and the criteria that influence satisfaction. Methods: This cross-sectional study involved 42 patients treated by year 4 and 5 dental students of the Kulliyyah of Dentistry, IIUM. Sampling was conducted using a single proportion formula, and patients were reviewed 2 weeks following placement of amalgam and composite restorations. Satisfaction was assessed using a self-administered five-point Likert scale questionnaire previously validated by a pilot study involving ten patients. Data were analyzed using independent sample t-tests and the Chi-square tests. Results: Patients were more satisfied with composite restorations than with amalgam restorations in terms of color and esthetics (P < 0.001). Other criteria, such as operator skills, treatment procedures, and external factors, had no significant effect on patient satisfaction with the restoration (P > 0.05). Overall, patient satisfaction with amalgam (81.0%) and composite restoration (88.1%) did not differ when restorations were placed by IIUM dental students. Conclusion: Most patients were satisfied with the amalgam and composite restorations placed by IIUM dental students. The color and esthetic value were the major criteria affecting patient satisfaction. Treatment procedures, operator skills, and external factors did not significantly influence patient satisfaction. Hence, in terms of satisfaction, amalgam remains a reliable material for use in restorative dentistry.